FISCAL SUSTAINABILITY. A NOTE FOR CABO VERDE - MENDES, Cassandro (Journal of Advanced Studies in Finance, 2016)
The present note aims to analyze the sustainability of the fiscal policies adopted by the government of Cabo Verde in the last two decades (1990-2013). We used time series techniques to derive our results. We tested the debt sustainability under two case scenarios by using the potential cointegration between the government expenditures and revenues (revenue with or without donations from international partners). The results from our data show that the fiscal policies adopted recently can be assumed to be sustainable only in the first scenario, when foreign donations are considered. If we exclude foreign donations from the government revenues, the hypothesis of non-sustainability cannot be rejected. These results show that fiscal reforms are needed to supplant the great dependence from Donors.